2021
DOI: 10.1002/jcsm.12752
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sarcopenia and acute muscle mass loss on long‐term outcomes in critically ill patients with intra‐abdominal sepsis

Abstract: Background Sarcopenia is a known risk factor for poor outcomes across many chronic diseases. The impact on outcomes of both pre-existing sarcopenia and acute muscle wasting (AMW) in acute critical illness caused by sepsis remain unclear. Methods We conducted a prospective longitudinal cohort study of critically ill patients with intra-abdominal sepsis utilizing abdominal computed tomography at sepsis onset to determine baseline skeletal muscle index (SMI). Biomarkers of inflammation and catabolism were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 42 publications
5
50
2
Order By: Relevance
“…We were able to identify low muscle mass using CT scans in 48% of our population, which is a lower frequency compared to the 65% reported in an Italian cohort using different cut-off values for low muscle identification (45.4 cm 2 /m 2 for males and 34.4 cm 2 /m 2 for females) [38]. In critically-ill septic patients, Cox Mc et al, reported a prevalence of baseline low muscle mass in 50% of patients [39]. Another study in hospitalized patients with COVID-19 showed that muscle mass was related to the need for ICU admission (17%), longer hospital LOS (mean, 10.8 days), and mortality (6.6%) [40].…”
Section: Discussioncontrasting
confidence: 55%
“…We were able to identify low muscle mass using CT scans in 48% of our population, which is a lower frequency compared to the 65% reported in an Italian cohort using different cut-off values for low muscle identification (45.4 cm 2 /m 2 for males and 34.4 cm 2 /m 2 for females) [38]. In critically-ill septic patients, Cox Mc et al, reported a prevalence of baseline low muscle mass in 50% of patients [39]. Another study in hospitalized patients with COVID-19 showed that muscle mass was related to the need for ICU admission (17%), longer hospital LOS (mean, 10.8 days), and mortality (6.6%) [40].…”
Section: Discussioncontrasting
confidence: 55%
“…As given in Table 1 , 10 cohort studies [ 16 25 ] including 2396 adult patients with sepsis were included in the meta-analysis. These studies were published between 2017 and 2021 and performed in Japan [ 16 , 18 , 25 ], Korea [ 19 , 21 23 ], China [ 17 ], Italy [ 20 ], and the United States [ 24 ]. All of the included studies were retrospective cohort studies, except for one study, which was a prospective cohort study [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies were published between 2017 and 2021 and performed in Japan [ 16 , 18 , 25 ], Korea [ 19 , 21 23 ], China [ 17 ], Italy [ 20 ], and the United States [ 24 ]. All of the included studies were retrospective cohort studies, except for one study, which was a prospective cohort study [ 24 ]. The studies included patients with sepsis admitted in emergency department or intensive care unit diagnosed with the sepsis-1 [ 20 ], sepsis-2 [ 17 ], and sepsis-3 criteria [ 16 , 18 , 19 , 21 25 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in contrast to present acute illness, sarcopenia is understudied in ICU settings. However, baseline LMM has been demonstrated to be a risk factor for poor prognosis in other diseases, including esophageal cancer [ 48 ], chronic obstructive pulmonary disease [ 49 ], and sepsis in critically ill patients [ 50 ]. Our review adds to the growing body of evidence suggesting that LMM is a strong predictor of poor outcomes among patients with MV.…”
Section: Discussionmentioning
confidence: 99%